66. Autonomic-sensory neuropathy onset in a patient with acute brainstem impairment – A case report. Issue 1 (January 2015) - Vigneri, S.; Rispoli, V.; Azzini, C.; Caniatti, M.L.; Tola, M.R.; Simioni, V.; Capone, J.G.; Sette, E.; Tugnoli, V.
<x xml:space="preserve">Abstract</x> Here we report on a 64-year-old Caucasian man admitted to the Neurology department due to a history of severe hypoacusia, nausea, stipsis, cerebellar ataxia and progressing consciousness impairment, which raised up the clinical suspicion of acute cerebellitis and suggested the introduction of oral corticosteroids. At day 7, a mild improvement of cerebellar symptoms was followed by the onset of orthostatic hypotension, four limb sensory impairment and areflexia. The spinal tap displayed a mild protein increase (78 mg/dl) and high-titer of anti-Hu (ANNA-1) antibodies in CSF. The same antibodies were also found after blood testing. Nerve conduction velocities (NCV) of the four limbs showed a picture of severe peripheral neuropathy with predominant sensory and axonal features, absence of sympathetic skin response. No sensory evoked potentials were detectable either at upper and lower limbs, while cranial district reflexes and NCV were not affected. Autonomic tests confirmed severe orthostatic hypotension with mild parasympathetic involvement. A PET study highlighted a hypercaptation in the right paratracheal region, which a bronchoscopy with transbronchial biopsy identified as a possible lung cancer. Therefore, the patient was diagnosed with dysimmune rhombencephalitis and polyneuropathy in a likely paraneoplastic syndrome.